2016
DOI: 10.1002/macp.201600232
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Gas-Transport Properties of Metathesis Polytricyclononenes Bearing Three Me3 Si Groups per Monomer Unit

Abstract: A new metathesis polynorbornene containing three SiMe3 groups per monomer unit directly connected to the norbornene moiety via SiC bonds is synthesized. The ring‐opening metathesis polymerization of sterically hindered 3,3,4‐tris(trimethylsilyl)tricyclononene‐7 is successfully conducted in yields 80–85% in the presence of first generation Grubbs catalyst. The corresponding polymer is obtained with molecular weight Mw up to 5.4 × 105 Da. It is an amorphous glassy (Tg = 200 °C) polymer with high thermal stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
(37 reference statements)
1
7
1
Order By: Relevance
“…Previously we have shown that the introduction of three SiMe 3 ‐groups directly attached to the norbornene structure (i.e., 3,3,4‐tris(trimethylsilyl)tricyclononene‐7) dramatically lowered monomer activity in metathesis polymerization in comparison with monomers containing only one or two SiMe 3 ‐groups . At the same time we observed a significant increase in gas permeability of the corresponding metathesis polymer having three SiMe 3 ‐groups per a monomer unit.…”
Section: Introductionsupporting
confidence: 92%
“…Previously we have shown that the introduction of three SiMe 3 ‐groups directly attached to the norbornene structure (i.e., 3,3,4‐tris(trimethylsilyl)tricyclononene‐7) dramatically lowered monomer activity in metathesis polymerization in comparison with monomers containing only one or two SiMe 3 ‐groups . At the same time we observed a significant increase in gas permeability of the corresponding metathesis polymer having three SiMe 3 ‐groups per a monomer unit.…”
Section: Introductionsupporting
confidence: 92%
“…Brunauer, Emmett, and Teller (BET) surface area of this polymer was 155 m 2 g −1 and total pore volume was 0.176 cm 3 g −1 (the mesopore volume was 0.075 cm 3 g −1 ). Although these values are not high and lower than similar characteristics for earlier studied addition polynorbornenes with side bulky Me 3 Si‐groups, they are much higher than for different metathesis polymers with bulky substituents or addition homopolymer from HexNB (BET surface area < 1 m 2 g −1 ). Mesopore and micropore size distributions were estimated using BJH and Horvath–Kawazoe methods accordingly ( Figure ).…”
Section: Resultscontrasting
confidence: 48%
“…The maximum mass increment was about 12%. This is in contrast to metathesis polynorbornenes containing internal double bonds in main chains: for them the increase of mass was not found in TGA curves in air . The oxidation of double bonds in poly(DCPD) was also observed at room temperature for polymer samples stored in air that was confirmed by IR spectroscopy (Figure S3, Supporting Information) and elemental analysis.…”
Section: Resultsmentioning
confidence: 78%
“…The polynorbornenes and polytricyclononenes bearing three Me 3 Si-groups per one monomer unit were found to be more permeable than their counterparts with two Me 3 Si-substituents in the same unit (Figs. 6, 7) [59,69,71,86]. An increase in the gas permeability composed 20-300% and depended on the binding patterns of Me 3 Si-substituents with the main chains.…”
Section: Effect Of the Number Of Me 3 Si-groups In A Monomer Unit On mentioning
confidence: 99%
“…The first one is based on the introduction of bulky and rigid silicon-containing substituents (i.e., Me 3 Sigroups) into the monomer units of polynorbornenes. As a rule, the gas permeability coefficients essentially grow with an increase in the number of these groups per a monomer unit [24,[69][70][71][72]. Another way to improve the permeability characteristics of polynorbornenes is the synthesis of polymers with rigid main chains.…”
Section: Approaches To the Production Of Highly Gas Permeable Siliconmentioning
confidence: 99%